Efficient and Stable Chemical Passivation on Perovskite Surface via Bidentate Anchoring. Issue 13 (14th February 2019) - Zhang, Hao; Wu, Yongzhen; Shen, Chao; Li, Erpeng; Yan, Chenxu; Zhang, Weiwei; Tian, He; Han, Liyuan; Zhu, Wei‐Hong
Abstract: Chemical passivation is an effective approach to suppress the grain surface dominated charge recombination in perovskite solar cells (PSCs). However, the passivation effect is usually labile on perovskite crystal surface since most passivating agents are weakly anchored. Here, the use of a bidentate molecule, 2‐mercaptopyridine (2‐MP), to increase anchoring strength for improving the passivation efficacy and stability synchronously is demonstrated. Compared to monodentate counterparts of pyridine and p ‐toluenethiol, 2‐MP passivation on CH3 NH3 PbI3 film results in twofold improvement of photoluminescence lifetime and remarkably enhanced tolerance to chlorobenzene washing and vacuum heating, which improve the power conversion efficiency of n–i–p planar structured PSCs from 18.35% to 20.28%, with open‐circuit voltage approaching 1.18 V. Moreover, the CH3 NH3 PbI3 films passivated with 2‐MP exhibit unprecedented humid‐stability that they can be exposed to saturated humidity for at least 5 h, mainly due to the passivation induced surface deactivation, which renders the unencapsulated devices retaining 93% of the initial efficiency after 60 days aging in air with relative humidity of 60–70%. Abstract : A specific bidentate molecule, 2‐mercaptopyridine, is demonstrated to substantially enhance anchoring strength at surface of metal halide perovskites, which improves the passivation efficacy and stability synchronously relative to monodentate counterparts. The highly stable bidentate anchoring based passivation on CH3 NH3 PbI3 not only advances power conversion efficiency from 18.35% to 20.28%, but also leads to a champion lifetime in humid air.